Feasibility of optimal vertex size and spacing for lattice radiotherapy implementation using helical tomotherapy - Seol, Yunji; Lee, Young Kyu; Kim, Byeong Jin; Choi, Kyu Hye; Hong, Ji Hyun; Park, Chan-beom; Kim, Sun Hwa; Park, Hyeong Wook; Kim, Jung-Il; Cheon, Wonjoong; Kang, Young-nam; Choi, Byung Ock (Frontiers in Oncology, 2025)
PurposeLattice radiotherapy (LRT), a type of spatially fractionated radiotherapy (SFRT), delivers high dose at specific volumes of lattice structure within the tumor to create a low valley-to-peak dose ratio (VPDR). This study aims to evaluate the feasibility of implementing SFRT using helical tomotherapy and to investigate the effects of vertex size and spacing for attaining the VPDR.MethodsA three-dimensional lattice structure with 3×3×3 vertices was designed in a cheese phantom. Vertex sizes of 0.5 cm, 1.0 cm, and 2.0 cm were assessed, with spacing from 1.0 cm to 5.0 cm. The prescribed dose was set to 20 Gy to the vertices in a single fraction. VPDR was calculated from dose profiles along lines connecting three vertices in the anterior-posterior (AP), lateral (LAT), and superior-inferior (SI) directions. The minimum, maximum, and mean dose for each vertex, as well as conformity, homogeneity and monitor unit (MU) analysis were also performed.ResultsVPDR decreased significantly with increasing vertex size and spacing. While the AP and LAT directions showed similar VPDR values, the SI direction consistently exhibited lower VPDR values across all configurations. Vertex sizes of 0.5 cm, 1.0 cm, and 2.0 cm required spacing of at least 3.0 cm, 2.0 cm, and 1.0 cm, respectively, to achieve VPDR values below 0.4. The conformity indices ranged from 1.0 to 4.02, and the homogeneity indices ranged from 1.20 to 1.57 across all configurations. Additionally, the MUs increased with both vertex size and spacing.ConclusionsThis study quantitatively analyzed the impact of various vertex sizes and spacings on VPDR in lattice radiotherapy using helical tomotherapy. VPDR decreased with increasing vertex size and spacing, with consistently lower values in the SI direction. These findings provide crucial insights for optimizing LRT plans. The identified relationships between the parameters and VPDR offer a foundation for developing more effective LRT protocols in helical tomotherapy, potentially improving therapeutic outcomes